Disfunción tiroidea como factor asociado a severidad en pacientes con artritis reumatoide de reciente diagnóstico atendidos en el Hospital Regional Docente de Trujillo, 2023 - Calvo Marcelo, Rodolfo Elvis (2023)
Rheumatoid arthritis (RA) is an unknown etiology systemic autoimmune disease that mainly affects the joints. As a chronic condition, it is commonly associated with other comorbidities, such as thyroid dysfunction disorders, with which it shares a genetic and autoimmune basis. According to some studies, thyroid dysfunction may influence an initial presentation with greater severity in patients with RA, carrying therapeutic and prognostic implications. The association between thyroid dysfunction and the severity of RA is a subject of debate in the scientific community. Therefore, the purpose of this study is to contribute to elucidate this association at a local level, as is the case with patients who attend the outpatient Rheumatology clinic at the Regional Teaching Hospital of Trujillo.